Preliminary adaptation into Portuguese of a standardised picture set for the use in research and neuropsychological assessment - POMPÉIA SABINE; BUENO ORLANDO F.A. (Arquivos de Neuro-Psiquiatria)
Pictorial stimuli and words have been widely used to evaluate mnemonic processes in clinical settings, neuropsychological investigations, as well as in studies on the mechanisms underlying the phenomena of memory. However, there seem to be few studies of standardisation of pictures for research in this field. The present paper aimed at adapting the use of a set of pictures standardised for English speaking subjects for Portuguese speakers. Name agreement of 150 pictures was assessed in 100 high-school students. Ninety pictures were found to present the same name for over 90 subjects. Results yield data that may help create more controlled tests for the study of memory for pictorial stimuli in Brazil.